A contrafação e a resiliência nas cadeias de suprimentos - Machado, Solange Gualberto da Mata (2016)
The globalization of markets has intensified exposure to the risk of counterfeiting, as well as increased the potential for disruptions within a supply chain. Issues related to counterfeiting have become complex and challenging because it is increasingly difficult to separate the licit from the illicit chains. Companies can take reactive and proactive position, but there is still a gap of how companies can become resilient against counterfeiting. For this to happen, the company needs to develop mitigation capabilities to be able to respond, recover, redesign and return to its normal performance. An exploratory study using the theoretical lens of risk management was carried out with four multinational and one domestic company. The objective of the study was to understand what are the capabilities developed in the process to become resilient against counterfeiting. The results showed that nine mitigation capabilities are developed in resilient companies. Not all of them are developed within the company. To maximize resources, companies choose to use the expertise in intellectual property of third party companies and focus on capabilities related to business. In addition, the research advances in the understanding of the development of mitigation capabilities and proposes the existence of two stages prior to resilience: reactive and proactive. Moreover, for each stage were identified a set of capabilities. In the first stage – named reactive – three capabilities were evident: trust and control, traceability and intellectual property internal capability. In the second stage – named proactive – four capabilities were identified: visibility, preparedness, supply chain internal and external collaboration and intellectual property external capability. In the last stage only one capability was evident: agility. Developing those nine capabilities increases the propensity of the company become resilient to counterfeiting.